Education 4.0 @ Enderun the changing dynamics in teaching and learning - Guanzon, Monette (Enderun Colleges Scholarly Review, 2020)
The objective of the paper is to present how education is being shaped by technological advances. Evaluating the implementation of technology aided teaching in Enderun Colleges, this gave the following results, the strong support coming from the students as learning became more digital. The institutional push for every faculty to implement and adapt the learning management system of the school was also noted.